Baking properties of different amaranth flours as wheat bread ingredients - Миколенко, Світлана Юріївна; Mykolenko, Svitlana; Жигунов, Дмитро Олександрович; Zhygunov, Dmitro; Руденко, Тетяна Вікторівна; Rudenko, Tetyana (Одеська національна академія харчових технологій, 2020)
Технологічні характеристики амарантового повножирового борошна залежать від сортових особливостей зерна амаранту української селекції і суттєво відрізняються від амарантового знежиреного борошна з пластівців і з крупи. Порівняно з пшеничним борошном вищого сорту, амарантове характеризується нижчою вологістю, вищою водопоглинальною здатністю і автолітичною активністю. Сорт амаранту Amaranthus hypochondriacus суттєво впливає на білість повножирового борошна, найбільш світлим з яких є борошно із зерна сорту Харківський-1. За рахунок більшого вмісту жиру і білків, клітковини амарантове борошно відрізняється вищою кислотністю. Водопоглинальна здатність борошна позитивно корелює з автолітичною активністю (+0.885). Кислотність негативно корелює з вологістю (-0.939) і білістю (–0.814) борошна. Хліб, виготовлений із заміною 5, 15, 25% пшеничного борошна вищого сорту на амарантове борошно різних видів, характеризується збільшеним питомим об’ємом виробів, зниженою формостійкістю хліба, збільшеною пористістю м’якушки. Статистично достовірною (р<0.05) є кореляція комплексної якості досліджуваних зразків хліба з питомим об’ємом (+0.540) та негативною з кислотністю (-0.685). Формостійкість негативно корелює з пористістю (-0.598), а питомий об’єм і пористість мають позитивний кореляційний зв'язок (+0.533). Питомий об’єм і пористість хліба при застосуванні амарантового повножирового борошна зростають у 1.1-1.3 і 1.1 разів відповідно. Використання знежиреного борошна з пластівців призводить до збільшення питомого об’єму виробів у 1.3-1.9, пористості – на 1.1-1.2 разів, з крупи – у 1.3-1.5 і 1.1-1.2 разів відповідно. Зразки хліба з 25% дозуванням амарантового борошна усіх досліджених видів і вироби з 15% повножирового борошна із зерна сорту Лєра характеризуються найнижчими споживчими якостями. Доведено, що використання 5-15% повножирового борошна із зерна амаранту сорту Харківський-1 та знежиреного борошна з пластівців і з крупи як побічних продуктів переробки зерна амаранту на олію підвищує якість хліба і дозволяє поліпшити його поживну цінність. - The technological properties of full-fat amaranth flour depend on the varietal characteristics of the Ukrainian amaranth grain and differ significantly from amaranth flour from flakes and amaranth flour from groats. In comparison with patent wheat flour, amaranth flour has a lower moisture content, higher water absorption capacity and autolytic activity. The variety of Amaranthus hypochondriacus significantly effects on the whiteness of full-fat flours, the lightest of which is obtained from the grain cultivar Kharkivsky-1. A higher fat, protein, and fibre content makes amaranth flours more acidic. The water absorption capacity of the flours shows positive correlation with their autolytic activity (+0.885). The acidity negatively correlates with the moisture (-0.939) and whiteness (-0.814) of the flours. Using amaranth flour of the different types to replace 5, 15, and 25% of patent wheat flour when making bread increases its specific volume and crumb porosity and decreases its shape stability. The positive correlation of the overall quality of the bread samples under study with their specific volume (+0.540) and the negative correlation with the acidity (-0.685) are statistically significant. The shape stability negatively correlates with the porosity (-0.598), and the latter positively correlates with the specific volume (+0.533). The use of full-fat amaranth flour increases the specific volume and porosity of bread by 1.1–1.3 and 1.1 times respectively. The use of defatted flour from flakes leads to a 1.3–1.9 -fold increase in the specific volume and to a 1.1–1.2 -fold increase in the porosity. Incorporation of amaranth flour from groats allows increasing the specific volume and porosity of bread by 1.3–1.5 and 1.1–1.2 times respectively. The bread samples with 25% of all amaranth flours considered and with 15% of full-fat flour of the Liera variety have the lowest consumer characteristics. It has been proved that using 5–15% of full-fat flour from the amaranth grain of variety Kharkivsky-1 and defatted flour from flakes and groats (by-products of processing amaranth grain into oil) improves the quality and nutritional value of bread.
Хлібопекарські властивості різних видів амарантового борошна як складової пшеничного хліба
Keywords: Amaranthus hypochondriacus; Amaranthus hypochondriacus; амарантове повножирове борошно; full-fat amaranth flour; амарантове знежирене борошно з пластівців; defatted amaranth flour from flakes; амарантове знежирене борошно з крупи; defatted amaranth flour from groats; пшеничний хліб; wheat bread; хлібопекарські властивості; baking properties